The Governance of Insurance Undertakings Corporate Law and Insurance Regulation - Marano, Pierpaolo; Noussia, Kyriaki (AIDA Europe Research Series on Insurance Law and Regulation, 2022)
This open access volume of the AIDA Europe Research Series on Insurance Law and Regulation brings together contributions from authors with different legal cultures. It aims to identify the legal issues that arise from the intersection of two disciplines: insurance law and corporate/company law. These legal issues are examined mainly from the perspective of European Union (EU) law. However, there are also contributions from other legal systems, enriching the perspective with which to approach these issues.